Hesperetin but not ellagic acid increases myosin heavy chain expression and cell fusion in C2C12 myoblasts in the presence of oxidative stress - Cuijpers, Iris; Dohmen, Colin G. M.; Bouwman, Freek G.; Troost, Freddy J.; Sthijns, Mireille M. J. P. E. (Frontiers in Nutrition, 2024)
Introduction: Skeletal muscle regeneration is impaired in elderly. An oxidative stress-induced decrease in differentiation capacity of muscle satellite cells is a key factor in this process. The aim of this study is to investigate whether orange polyphenol hesperetin and pomegranate polyphenol ellagic acid enhance myoblast differentiation in the presence and absence of oxidative stress, and to explore underlying mechanisms.Methods: C2C12 myoblasts were proliferated for 24h and differentiated for 120h while exposed to hesperetin (5, 20, 50µM), ellagic acid (0.05, 0.1µM) or a combination (20µM hesperetin, 0.05µM ellagic acid) with and without oxidative stress-inducing compound menadione (9µM) during 24h of proliferation and during the first 5h of differentiation. The number of proliferating cells was assessed using fluorescent labelling of incorporated 5-ethynyl-2'-deoxyuridine. Myosin heavy chain expression was assessed by fluorescence microscopy and cell fusion index was calculated. Furthermore, protein expression of phosphorylated p38 and myomixer were assessed using Western blot. Results: None of the compounds induced effects on cell proliferation. Without menadione, 20µMhesperetin increased fusion index by 7.1% compared to control (p=0.03), while ellagic acid did not affect measured parameters of differentiation. Menadione treatment did not change myosin heavy chain expression and fusion index. In combination with menadione, 20µM hesperetin increased myosin heavy chain expression by 35% (p<0.01) and fusion index by 7% (p=0.04) compared to menadione.Furthermore, the combination of menadione with hesperetin and ellagic acid increased myosin heavy chain expression by 35% compared to menadione (p=0.020). Hesperetin and ellagic acid did not change p38 phosphorylation and myomixer expression compared to control, while treatment with menadione increased p38 phosphorylation (p<0.01) after 5h and decreased myomixer expression (p=0.04) after 72h of differentiation.Hesperetin increased myosin heavy chain expression in the presence of oxidative stress induced by menadione, and increased cell fusion both in the presence and absence of menadione. Ellagic acid did not affect the measured parameters of myoblast differentiation. Therefore, hesperetin should be considered as nutritional prevention or treatment strategy to maintain muscle function in age-related diseases such as sarcopenia. Future research should focus on underlying mechanisms and translation of these results to clinical practice.